THE RADICAL HUMANISM OF SYLVIA WYNTER: AN INTRODUCTION - Paterniani, Stella Zagatto [UNESP]; Belisário, Gustavo; Nakel, Laura (FapUNIFESP (SciELO), 2022)
This article aims to present the Brazilian audience to the work of Sylvia Wynter, a Jamaican intellectual, artist and activist. We begin the text with elements of the historical contextualization of Jamaica and the Caribbean, with an emphasis on the deleterious effects of the plantation system and imperialism on the constitution of Black people, followed by some biographical notes on Wynter. Finally, we present some of her analytical, political and theoretical contributions, for which we emphasize three aspects. First, her critique of merging humanity with the western concept of Man, and the epistemological and analytical proliferation of Man. Second, her call for an epistemic reconstruction of the university and the seminal role of Black studies in this endeavor, as well as a critique of the pacification of Black studies when incorporated as ethnohistory. Finally, we present her proposal for radical humanism.
EL HUMANISMO RADICAL DE SYLVIA WYNTER: UNA PRESENTACIÓN
O HUMANISMO RADICAL DE SYLVIA WYNTER: UMA APRESENTAÇÃO
Keywords: Antiblackness; Black studies; Humanism; Humanity; Sylvia wynter